Headwater stream ecosystem: an important source of greenhouse gases to the atmosphere. (15th February 2021) - Li, Mingxu; Peng, Changhui; Zhang, Kerou; Xu, Li; Wang, Jianming; Yang, Yan; Li, Peng; Liu, Zelin; He, Nianpeng
Highlights: Reduction of riverine GHG fluxes across the stream order Reverse dependency of riverine GHG concentration and DO level High GHG fluxes occur in headwater streams Studies on riverine GHGs should focus more on headwater regions Abstract: Although an increasing number of reports have revealed that rivers are important sources of greenhouse gases (GHGs), the magnitude and underlying mechanism of riverine GHG emissions are still poorly understood. The global extent of the headwater stream ecosystem may represent one of the important GHG emitters. A global database of GHG measurements from 595 rivers, indicated that the concentrations of riverine GHGs continually decrease as the stream order increases. Further analysis suggested that high GHG emissions from headwater streams (Strahler stream orders of 1 to 3) could be related to the low levels of dissolved oxygen, massive terrestrially derived carbon/nitrogen inputs and large gas exchange velocity. Through a combination of the predicted river surface areas and gas transfer velocities, we estimated that globally, the rivers emit approximately 6.6 (5.5–7.8) Pg CO2, 29.5 (19.6–37.3) Tg CH4, and 0.6 (0.2–0.9) Tg N2 O per year, and totally emit 7.6 (6.1–9.1) CO2 equivalent into atmosphere per year. The headwater streams contribute 72.3%, 75.5%, and 77.2% of the global riverine CO2, CH4, and N2 O emissions, respectively. This study presents a systematic estimation of GHG emissions from river ecosystems worldwide and highlights the dominant role played by headwater streams in GHG evasions from global rivers. Graphical_Abstract: Image, graphical abstract